POLA PEMASARAN DAN KETERSEDIAAN PUPUK PASCA KEBIJAKAN PENGENDALIAN DISTRIBUSI PUPUK UREA MARET 2001 - ILHAM, NYAK (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Free trade policy which is hope could avoid scarcity of fertilizer, at the end was causing the condition of fertilizer scarcity. This condition push the government to replied the policy of urea control distribution. This research has an objective to evaluate the impact of these policy to marketing efficiency and fertilizer supply. Data and information was gathered by using Rapid Rural Appraisal Method in some level of respondent in Kabupaten Subang and Garut on February 2001. The data was analysed by using description method with cross tabulation. The result of these analysis showed that the impact of urea control distribution government supply with small variants of price. In the other way, for producer and traders this policy was give disincentive to them, but on the other hand their marketing systems quite efficient. We still found some weakness factor which is caused the minimum function of dealers/distributors, this all caused by unfairness between them. The indicate analysis showed that comparable fertilizer use was not applied yet. To create sustainability in fertilizer distribution, the unfairness should be eliminate. To control the price of fertilizer could be done as follows: (1) to push raw material price. In this case natural gases; (2) To delete the obligation of Pusri in using storage in the Pusri fertilizer port; (3) to suggest value added tax 10 percent in fertilizer selling process, by this scenario we assumed that it will help them to use comparable fertilizer so the extension to farmer will keep continue.
Keywords: Marketing efficiency, Fertilizer Supply, Control Policy, Distribution